Multi-stage optimal control of lignocellulosic bioethanol production - Duarte, Florencia (2020)
The dynamics of production and purification of ethanol from sorghum lignocellulosic materials by a three stages process was modeled and optimized in this work. The process involves a first stage for hydrolyzing sweet sorghum bagasse; a second stage for fermenting the generated sugars and a third stage for the separation of ethanol. Kinetic and distillation equations were embedded into macroscopic balances in order to derive a mathematical model used to solve a three-stage optimal control problem. The aim was to maximize the process productivity by optimally managing the controlled flows between units and by optimally fixing switching times between the process stages.